(untitled) (Research, Society and Development, 2023)
Prostate cancer screening is based on clinical suspicion and the PSA antigen, which, when altered, directs the patient to perform a prostate biopsy. The use of multiparametric magnetic resonance imaging (mpNMR) with the PI-RADS v2 method helps to increase the accuracy of the biopsy. The aim of this study is to compare results of multiparametric magnetic resonance analysis based on the PIRADS v2 system with anatomopathological analysis of patients undergoing prostatic biopsy. This is a quantitative, observational, analytical, retrospective study. The analysis of the anatomopathological results of prostate biopsies of 60 patients previously submitted to mpNMR, from January 2017 to January 2019. The mean age of the 60 patients was 62.9 ± 10.0 (41-86), 45 of them (75%) had PSA levels greater than or equal to 4 ng/ml and in 15 patients (25%) the antigen was less than 4 ng/ml. The sensitivity of PSA in this study was 100% and its specificity was 28.8%. Sixty reports of prostatic biopsies were analyzed, in which their distribution showed 34 (56.6%) without alterations corresponding to a clinically significant tumor, the other 26 patients (43.3%) presented alterations. The sensitivity and specificity of mpMRI with the PI-RADS v2 system in detecting tumors was 75% and 80.7% respectively. It was demonstrated in this study that using mpMRI with the PI-RADS v2 system was efficient in estimating clinically significant tumors and helping in medical management.